2010
DOI: 10.1007/s10663-010-9123-6
|View full text |Cite
|
Sign up to set email alerts
|

The border effects in Spain: an industry-level analysis

Abstract: Esta es la versión de autor del artículo publicado en:This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscriptionThe border effects in Spain: an industry-level analysisFrancisco Requena • Carlos LlanoAbstract A gravity-model approach is used to estimate the magnitude of the internal border (home bias) and external border (frontier) effects in Spain using industry-level trade flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
5
25
0
1
Order By: Relevance
“…In the second column, the intraregional flows are controlled including the border effect dummy 'ownreg'. The 'border effect' coefficient estimate (3.984) is very large and consistent with other empirical findings regarding border effects in Spain, for industries such as 'Chemical products' or 'Non-metallic minerals' (Ghemawat et al 2010;Requena and Llano 2010). In this case, this large border effect is not expected to be driven by an external barrier to trade.…”
Section: Estimation Resultssupporting
confidence: 87%
“…In the second column, the intraregional flows are controlled including the border effect dummy 'ownreg'. The 'border effect' coefficient estimate (3.984) is very large and consistent with other empirical findings regarding border effects in Spain, for industries such as 'Chemical products' or 'Non-metallic minerals' (Ghemawat et al 2010;Requena and Llano 2010). In this case, this large border effect is not expected to be driven by an external barrier to trade.…”
Section: Estimation Resultssupporting
confidence: 87%
“…The two additional variables are included as extra factors that facilitate trade (sharing a border with Portugal, BP, and with France, BF) are negative and positive signed, respectively, although the variable border with Portugal is not statistically significant in the baseline regression. According to the results in column 1 of Requena and Llano, 2010). This border effect (column 1 of Table 3) is slightly higher than in the estimations of McCallum (1995), which showed that Canadian cross-provincial trade was 22 times larger than cross-border trade with states in the United States.…”
Section: Resultsmentioning
confidence: 59%
“…Gravity models began to obtain sound theoretical groundings from the 1970s onwards after being applied to various contexts in economics (Anderson, 1979;Bergstrand, 1985Bergstrand, , 1989Helpman and Krugman, 1985;Breuss and Egger, 1999;Anderson and van Wincoop, 2003;Requena and Llano, 2010). An analogy of Newton's gravitational attraction, the basic model considers that bilateral trade flows depend positively on the income of the two economies and negatively on the distance that separates them, apart from including other dummy variables that capture the qualitative effects that influence the exports of a country (language, border, etc.…”
Section: Theoretical Frameworkmentioning
confidence: 99%